Self-efficacy in preservice teachers preparing to teach religious education - Noseda, Mary (Journal of Religious Education, 2020)
Teacher self-efficacy is understood as a teacher's belief in his or her ability to successfully accomplish a specific teaching task in a particular context. Studies have been undertaken to determine preservice teachers' self-efficacy in particular curriculum areas, but none have been completed that relate to the teaching of Religious Education (RE). This article reports on the findings of research undertaken with a group of preservice teachers preparing to teach RE in Catholic secondary schools in Melbourne, Victoria. The preservice teachers (PSTs) were enrolled in the Graduate Certificate in Religious Education (GCRE), which is the qualification undertaken by preservice teachers at Australian Catholic University (ACU). The course consists of four units—two in theology and two in RE. A group of preservice teachers at Australian Catholic University who were enrolled in the GCRE were asked to participate in the research about their self-efficacy to teach RE. The results of the research outlines the importance of self-efficacy to the task of teaching and to teaching of the specialist area of RE in Catholic schools. The outcomes of the research indicated that the group of preservice RE teachers had higher levels of self-efficacy to teach RE at the end of the unit than they had at the beginning. This finding, which confirmed research conducted in other curriculum areas, was that preservice teachers' self-efficacy was enhanced by their participation in the unit.